Anthropomorphic Metaphorical Features in Figurative Content of ISLAND Concept - T. P. Karpukhina; A. V. Lugovskoy (Научный диалог)
The problem of actualization of anthropomorphic metaphorical features in the figurative content of the ISLAND concept is considered. The object of the research is the ISLAND concept as a cultural concept. The subject of the research is the anthropomorphic metaphorical features included in the figurative content of the ISLAND concept, and the means of their linguistic verbalization. On the basis of the classifications of the main types of metaphorical transfers and the main types of figurative-metaphorical signs in the content of the concept, a classification of anthropomorphic metaphorical signs that are included in the figurative content of the ISLAND concept is proposed. As a result of the analysis, five main groups of anthropomorphic metaphorical features have been identified: 1) gender; 2) physiological properties; 3) somatic affiliation; 4) the physical properties of a person; 5) mental properties. It is shown that the feature of the female is present in the figurative content of the concept under study. It is noted that such parts of the human body as the head, heart, spine, as well as physical actions: coming, lying, standing, etc. are most often metaphorized. A number of physiological and mental properties of a person are revealed, which are subject to metaphorization: the ability to live, visual ability, feelings of happiness and tranquility.